A unique sarcopenic progression in the mouse rotator cuff. Issue 1 (28th October 2021) - Meyer, Gretchen A.; Shen, Karen C.
Abstract: Background: In response to chronic injury, the muscles of the rotator cuff (RC) experience a unique degeneration characterized by extensive fatty infiltration and loss of contractile function. Human studies suggest this degeneration is also a feature of RC sarcopenia and may precede RC injury. In this study, we investigated whether RC muscles exhibit a similar unique sarcopenia in the mouse. Methods: Male and female mice were subdivided into four age groups: 3, 9, 18, and 24 months. The supraspinatus (SS) and infraspinatus muscles of the RC and the tibialis anterior (TA) muscle of the hindlimb were assessed. Muscle mass, contractile function, fibre cross‐sectional areas and numbers, fatty infiltration, and fibrosis were assessed at each time point. Targeted transcriptional analyses were performed to assess the role of metabolic and inflammatory derangement in the pathology. Results: The 24‐month‐aged female mice exhibited decreased mass (25% lower than at 9 and 18 months, P  < 0.01) in all muscles tested. However, only RC muscles also exhibited decreased contractile tension at this time point (20% lower than at 18 months, P  < 0.005). Similarly, only female RC muscles exhibited increased fatty infiltration at 24 months (20% higher than 9 months, P  < 0.05) and had elevated transcriptional markers of adipogenesis (2.4‐fold higher Pparg and 3.8‐fold higher Adipoq expression compared with 9 months, P  < 0.001). Unbiased metabolic transcriptional profiling identified up‐regulation of the antigen presentation ( Z scores of 2.3 and 1.9 for SS and TA, respectively) and cytokine and chemokine signalling ( Z scores of 3.1 and 2.4 for SS and TA, respectively) pathways in 24 month female muscle compared with 9. Further transcriptional analysis supported increased expression of pro‐adipogenic inflammatory signals (6.3‐fold increase in Il6 and 5.0‐fold increase in Anxa2, P  < 0.01) and increased presence of fibro‐adipogenic progenitors (2.5‐fold) in the 24‐month‐aged female RC compared with 9 months that together exacerbate fatty infiltration. Conclusions: These data indicate that female mice replicate the unique sarcopenic pathology in the ageing human RC. Furthermore, they suggest that the exacerbated fatty infiltration is due to an interaction between higher resident fibro‐adipogenic progenitor numbers and an elevated systemic inflammation in aged female mice. We conclude that female mouse RC muscle is a novel system to study both human RC degeneration and the signals that regulate sarcopenic fatty infiltration in general, which is prevalent in humans but largely absent from the rodent hindlimb.